Domestic Violence and Social Justice: A Structural Intersectional Framework for Teaching About Domestic Violence. (October 2016) - Coker, Donna
My Domestic Violence and Social Justice law school course is organized around a structural intersectional framework to encourage students to recognize how structural inequalities inform the types of abuse perpetrated, individual and community responses to abuse, meanings that a victim ascribes to abuse, and factors that increase the risk of abuse. The course challenges the dominant neoliberal ideology focus on individual responsibility that eclipses shared responsibility. The course combines experiential exercises, a presentation by members of a community-based survivor organization, discussion of a hypothetical case with a legal practitioner, and court observation to help students apply theoretical insights to practical issues of individual representation and policy-making.